ANALISIS FAKTOR PENENTU EKONOMI MAKRO DAN SPESIFIK PERUSAHAAN DALAM MENENTUKAN HARGA SAHAM INDUSTRI KEUANGAN - Kurniawan, Desya Mitasari (Program Studi Ekonomi Pembangunan, 2022)
This study aims to determine the effect of macroeconomic and company-spesific factors in determining the stock price of financial industry. The independent variables used are Inflation, Economic Growth Return on Asset (ROA), Net Profit Margin (NPM), dan Earning per Share (EPS). While the dependent variable is the stock price. Research data taken by purposive sampling method, wich means that sampling with certain criteria. The object of this research is an insurance company listed on the Indonesian Stock Exchange from 2014 to 2020. Data analysis technique is panel data regression. The results of the study are inflationand net profit margin (NPM) have a negative effect on stock prices, economic growth and return on asset (ROA) have no significan effect on stock prices, and earning per share (EPS) has a positive effect on stock prices. Based on the result of the study, investors are encouraged to pay attention to and understand the factors that influence stock prices before make a decision to invest, so investors can make the right decisions in order to get maximum profit.